Effect of brown algae as biofertilizer materials on pepper (Capsicum annuum) growth, yield, and fruit quality (Asian Journal of Agriculture, 2024)
Abstract. Baroud S, Tahrouch S, Hatimi A. 2024. Effect of brown algae as biofertilizer materials on pepper (Capsicum annuum) growth, yield, and fruit quality. Asian J Agric 8: 25-31. Our study aims to evaluate the effect of three brown algae, Cystoseira gibraltarica (Sauvageau) P.J.L.Dangeard, Bifurcaria bifurcata R.Ross, and Fucus spiralis L., as biofertilizers on pepper (Capsicum annuum L.). These three algae were applied in two forms and at different concentrations: amendment (C1, C2, and C3) and concentrations of aqueous extract (0.5%, 1%, and 2%). Generally, the studied parameters were significantly improved using the aqueous extracts or the amendment at low concentrations. Indeed, the extract of F. spiralis at 1% shows a maximum length of the aerial and root parts (75.8 and 33.2 cm, respectively) and the dry weight of the plants (9.88 g). Aqueous extracts of F. spiralis at 1% show the maximum values of organic matter and nitrogen content of pepper leaves (88.3% and 4.4%, respectively). In addition, the 0.5% B. bifurcata extract presented significant values for the number of flowers (8.8 flowers/plant), and the 1% F. spiralis extract showed a better result for the number of fruits (7.1 fruits/plant). The alga C. gibraltarica at 1% showed a maximum fruit weight (82.65 g). On the other hand, F. spiralis at 1% showed maximum values of fruit diameter (48.33 mm). Similarly, F. spiralis at 0.5% showed maximum values in brix and sugar content (5.33% and 5.4%, respectively). These three algae were found to be effective and good candidates for the efficient development of biostimulants to improve growth and yield as well as the fruit quality of pepper. This study provides important information on identifying and utilizing Moroccan algal resources in agriculture.
Keywords: Algal fertilization, extract and amendment, fruit quality, growth, yield